2020
DOI: 10.1123/apaq.2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Inclusiveness of Integrated Physical Education From the Perspectives of Adults With Visual Impairments

Abstract: The purpose of this study was to examine the perspectives of individuals with visual impairment toward inclusion and the inclusiveness of their integrated physical education experiences. A retrospective, qualitative-description research approach was used, and 10 adults (age 20–35 years) with visual impairments acted as the participants. The data sources included one-on-one telephone interviews and reflective interview notes. A theoretical thematic analysis approach was used to analyze the data. Three interrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
3
30
0
1
Order By: Relevance
“…The subjective construction of PE by individuals with visual impairments has become of increasing interest over the past few years. Generally speaking, however, this body of research has largely examined the reflections of adult participants with visual impairments (Haegele & Kirk, 2018; Haegele et al, 2018; Haegele, Hodge, et al, 2019; Haegele & Zhu, 2017), with few studies focusing specifically on subjective constructions of PE by CWVI (Haegele & Buckley, 2019; Tanure Alves et al, 2018). A number of salient features of constructed experiences in mainstream PE have been exposed in this area of inquiry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjective construction of PE by individuals with visual impairments has become of increasing interest over the past few years. Generally speaking, however, this body of research has largely examined the reflections of adult participants with visual impairments (Haegele & Kirk, 2018; Haegele et al, 2018; Haegele, Hodge, et al, 2019; Haegele & Zhu, 2017), with few studies focusing specifically on subjective constructions of PE by CWVI (Haegele & Buckley, 2019; Tanure Alves et al, 2018). A number of salient features of constructed experiences in mainstream PE have been exposed in this area of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, while some positive experiences may be available, participants across studies appear to construct negative or challenging experiences in association with their PE in mainstream contexts. These negative experiences appear to be informed by instances of being bullied or ostracized by peers (Haegele, Hodge, et al, 2019; Haegele & Zhu, 2017), as well as being removed or isolated from activities by physical educators or paraeducators because of perceptions of inability (Tanure Alves et al, 2018). Importantly, CWVI have reported that physical educators may unknowingly influence social dynamics by communicating ideals of inability while belittling or discriminating against CWVI in front of peers without visual impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Students remain alert and attention owing to presence of two teachers as one of them teaches and the other observes. The integrated lectures may help the students to put together the learnt facts so as to get the whole picture and adopt a holistic approach while applying them to clinical practice (13).…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, more students with disabilities, including those with visual impairments, are being educated in integrated physical education classes with their peers without visual impairments than ever before (Haegele, 2019). The term integrated is used purposefully throughout this article to highlight the educational placement or setting in which students with visual impairments receive their education with students without disabilities (Haegele et al, 2020). This term is distinct from the term inclusive which refers to educational experiences which are guided by philosophies associated with inclusion whereby individuals with various learning styles and education needs experience a sense of belonging, acceptance, and value within a group (Spencer-Cavaliere, & Watkinson, 2010; Stainback & Stainback, 1996).…”
mentioning
confidence: 99%
“…This term is distinct from the term inclusive which refers to educational experiences which are guided by philosophies associated with inclusion whereby individuals with various learning styles and education needs experience a sense of belonging, acceptance, and value within a group (Spencer-Cavaliere, & Watkinson, 2010; Stainback & Stainback, 1996). Thus, as explained by Haegele (2019; p. 388), “an important distinction is that while inclusion as a philosophy promotes successful learning for students with a variety of learning and education needs (Block, 1999), integration more simply refers to the setting in which education occurs.” When examining literature pertaining to physical education experiences among persons with visual impairments in integrated contexts, predominately challenging experiences have been reported (Alves et al, 2018; de Schipper et al, 2017; Haegele et al, 2020; Haegele & Zhu, 2017). For example, research has demonstrated that it is not uncommon for students with visual impairments to be treated inequitably by their physical education teachers, including being removed or isolated from activities, because of perceptions of inability (Lieberman et al, 2006).…”
mentioning
confidence: 99%